Iterative Design and Evaluation of a Low-Code Development Platform for Welding Robot Control - Schenkenfelder, Bernhard; Moser, Michael; Pfeiffer, Michael; Pichler, Josef; Salomon, Christian; Winterer, Mario (Proceedings (IEEE International Conference on Emerging Technologies and Factory Automation), 2023)
A Low-Code Development Platform (LCDP) enables people with little or no software development training to create software applications. Unlike traditional textual programming environments, it provides tools that are more natural to the users, such as visual programming. By raising the level of abstraction beyond code, an LCDP empowers those who need software to develop it, bridging the gap between the growing demand for industrial software and the ability to deliver it. In this paper, we present an iterative, user-centered approach for developing an LCDP for welding robot control that replaces a system based on the C programming language. Findings indicate that an iterative approach, active user participation, usability evaluations, and paper prototyping all favor the successful development of an industrial LCDP.